Сучасні підходи до запровадження дошкільної дизайн-освіти - Матвієнко, С. І. (My University, 2018)
У статті розглянуто основні підходи щодо запровадження основ дитячого дизайну до роботи з дошкільниками. Визначено форми та методи роботи, в яких даний вид діяльності представлений у сучасній практиці закладів дошкільної освіти.
Modern approaches to the introduction of primary design education
The article describes the main approaches to the introduction of the basics of children's design in working with pre-schoolers. The forms and methods of work in which this type of activity is presented in modern practice of preschool education institutions are defined
Keywords: дитячий дизайн; children's design